2012
DOI: 10.1186/1746-1596-7-130
|View full text |Cite
|
Sign up to set email alerts
|

Can p63 serve as a biomarker for giant cell tumor of bone? A Moroccan experience

Abstract: BackgroundMultinucleated giant cell-containing tumors and pseudotumors of bone represent a heterogeneous group of benign and malignant lesions. Differential diagnosis can be challenging, particularly in instances of limited sampling. The purpose of this study was to evaluate the contribution of the P63 in the positive and differential diagnosis of giant cell tumor of bone.MethodsThis study includes 48 giant cell-containing tumors and pseudotumors of bone. P63 expression was evaluated by immunohistochemistry. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 12 publications
(26 reference statements)
2
14
1
1
Order By: Relevance
“…Recently, Yanagisawa et al reported that the highest scores of p63 expression are found in tumours that recur [9]. Contrary to earlier studies on the diagnostic value of p63 expression in giant-cell rich lesions [4,5], we and others [10,11] found wider expression also in chondroblastoma and ABC, which are the main differential diagnoses. Like De la Roza et al [10], we found p63 expression in some RG but with a low number of stained cells (mean=4.5 %).…”
Section: Utility Of P63 Ihc For a Diagnosis Of Benign Giant Cell-richcontrasting
confidence: 80%
“…Recently, Yanagisawa et al reported that the highest scores of p63 expression are found in tumours that recur [9]. Contrary to earlier studies on the diagnostic value of p63 expression in giant-cell rich lesions [4,5], we and others [10,11] found wider expression also in chondroblastoma and ABC, which are the main differential diagnoses. Like De la Roza et al [10], we found p63 expression in some RG but with a low number of stained cells (mean=4.5 %).…”
Section: Utility Of P63 Ihc For a Diagnosis Of Benign Giant Cell-richcontrasting
confidence: 80%
“…TP63 expression was observed mainly in the epithelial cells lining of radicular cysts, but also in the nuclei of a few mononuclear cells in the granulation tissues of radicular cyst, apical abscess and periapical granulomas. Interestingly, while TP63 expression is most commonly associated with epithelial cells, studies have shown that it may be expressed in stromal cells of giant cell tumours of the bone (Dickson et al 2008, Lee et al 2008, de la Roza 2011, Hammas et al 2012, Lau et al 2013, Shooshtarizadeh et al 2016, as well as in neoplastic lymphocytes in patients with non-Hodgkin's lymphoma (Hedvat et al 2005, Park & Oh 2005, Deel et al 2016. Additionally, although TP63 expression is commonly detected in the cell nuclei, studies have found cytoplasmic TP63 expression in lung, prostate and skin cancers (Narahashi et al 2006, Dhillon et al 2009, Matin et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…The multinucleated giant cells and mononuclear cells were positive for CD68, 10 RANK, 11 and cathepsin K 12 by immunohistochemistry, but were negative for p63. 13 14 15 The nuclear shapes of the mononuclear cells were not similar to those of the multinucleated giant cells. The cellular and nuclear atypia of these cells was mild.…”
Section: Discussionmentioning
confidence: 91%